Diabetes and dementia links - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionThe number of patients suffering from diabetes mellitus is growing globally. It is expected to observe 253.4 million sufferers in geriatric population in 2045. In this time, also 131.5 million of people is going to have dementia and other cognitive problems. In people aged over 65 these two diseases are concomitant quite often. What are the connections in the area of etiology and treatment?AimThe purpose of this study is to present links between dementia and diabetes are depicted in professional literature.ResultsDiabetes and dementia are associated on many levels. These conditions have common risk factors. Diabetes may contribute to cognitive impairment in many ways, promoting development of atherosclerosis, brain vessel damage and vascular dementia. Alzheimer disease may be promoted by hyperglycemia and hyperinsulinemia. On contrary also hypoglycaemia, often met in elderly diabetic patients has negative impact on cognitive function. Dementia seriously affects treatment of diabetes. The main problems are not satisfying adherence and diabetes self-management. Conclusions Prevention of diabetes and dementia risk factors can be performed simultaneously as the are common for both diseases. Enhancing physical activity, reducing saturated fats consumption, levels of cholesterol and body mass are considered to be beneficial in the context of described conditions. Furthermore, treatment of diabetes is strongly affected by cognitive dysfunction. Management of dementive diabetics requires individualization and using long-acting drugs. It is crucial to reduce risk of life-threatening hypoglycaemias and to create wide team to take care of these patients.